THE INFLUENCE OF CUSTOMER BRAND IDENTIFICATION AND PERCEIVED VALUE TOWARDS BRAND LOYALTY (A STUDY OF PLAYSTATION 4 PRODUCT OF SONY COMPUTER ENTERTAINMENT INC. IN MALANG CITY) - Pamungkas, Dhira Dharma Arya (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to know the influence of Customer Brand Identification and Perceived Value towards Brand Loyalty (A Study of PlayStation 4 Product of Sony Computer Entertainment Inc. In Malang) partially. The type of this research is explanatory research that explains the causal relationship between variables by hypothesis testing. This research was using questionnaire and literature study to collect the data. One hundred and thirty samples are used for this research which the owners of PlayStation 4 in Malang were filling the questionnaires, the sampling technique used was purposive sampling. Validity test, reliability test, and classical assumption test were the instruments used to test this research. Analytical methods used is path analysis and hypothesis testing was conducted by using t test. The result of this research shows that partially, by using t test it can be concluded that Customer Brand Identification (CBI) has direct significant effect towards Perceived Value, and Perceived Value has direct significant effect towards Brand Loyalty. CBI also has direct significant effect towards Brand Loyalty and indirect significant effect towards Brand Loyalty through Perceived Value. Â Keywords: Customer Brand Identification (CBI), Perceived Value, Brand Loyalty, PlayStation 4.